A study on users' perception towards cash card usage in UPM - Ismail, Maizatul Akmar (2001)
One of the most important significance in the emergence of e-commerce is the development of electronic payment system. This system replaces physical banknote and coins and substitutes them with electronic cash or digital cash. Smart cards used in electronic cash transactions are referred to stored-value cards or electronic purse i.e. the card will be considered as the repository for money. Units of value are stored on the card as the electronic equivalent of cash and later used for purchases. It can also be used to store value as credits for goods and services - for example, ticketing or canteen facilities. The introduction of new electronic payment scheme for substituting cash especially in Malaysia may be considered in its early age. The Malaysian Electronic Payment System (MEPS) has introduced MEPS Cash smart card as a new method of payment in the middle of year 1999. The method is expected to handle the rapid changes of technological advancement in creating the cashless society. However, consumer acceptances towards the new method of payment has not so far being tested. The consumer preference of using cash for personal consumption expenditures is still widening. On the other hand, money suffers from a few drawbacks that make it no longer practical as it took a lot of space, it cannot be transferred by any means of telecommunication network and finally, high transaction cost for handling money. This research was conducted in order to find a business model for a new method of payment i.e. by using smart card and to solve some of the existing problems that arise when using money in conventional way. The second objective of this research was to develop a smart card application prototype for the mentioned business model. This research focused on measuring user acceptance for the developed prototype and user perception towards the smart card as stored value card. The smart card business model, was then translated into a system, which showed the flow of the processes in smart card transaction. The processes clearly showed what happened between the three parties involved in the system: smart card user, merchant and bank. Selected students from the Faculty of Computer Science and Information Technology, UPM then evaluated the system by completing a questionnaire. The questionnaire intended to obtain the general background of the respondents, their attitudes towards smart card usage, acceptance towards cash card illustrated transaction processes. It was also aimed to obtain respondents' opinion if the smart card as stored value card were introduced in the near future. The result showed that the respondents are actually agreed and satisfied with the system in terms of its clarity and user interface. The findings also ascertained that it could increase the respondents' perception regarding reliability and level of convenience towards the usage of smart card. The fact that more than ninety percent of the respondents were willing to use the smart card for shopping indicated that consumer have no problem in accepting such system in the future.